2019
DOI: 10.3390/s19204533
|View full text |Cite
|
Sign up to set email alerts
|

Perturbation Analysis of a Multiple Layer Guided Love Wave Sensor in a Viscoelastic Environment

Abstract: Surface acoustic wave sensors have the advantage of fast response, low-cost, and wireless interfacing capability and they have been used in the medical analysis, material characterization, and other application fields that immerse the device under a liquid environment. The theoretical analysis of the single guided layer shear horizontal acoustic wave based on the perturbation theory has seen developments that span the past 20 years. However, multiple guided layer systems under a liquid environment have not bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…These issues could be addressed by an established etching procedure on quartz as well as the structural similarity between LGS and quartz [70]. According to this [71] explored that hardness could arrive from various sources and instances involving high temperature and pressure, radiation, harsh chemicals, high vibration, and so on. It has also exposed the SAW resonator originating from a piezoelectric thin film of the AlN layer on the sapphire substrate.…”
Section: Application Of One Port Multilayer Saw Resonatormentioning
confidence: 99%
“…These issues could be addressed by an established etching procedure on quartz as well as the structural similarity between LGS and quartz [70]. According to this [71] explored that hardness could arrive from various sources and instances involving high temperature and pressure, radiation, harsh chemicals, high vibration, and so on. It has also exposed the SAW resonator originating from a piezoelectric thin film of the AlN layer on the sapphire substrate.…”
Section: Application Of One Port Multilayer Saw Resonatormentioning
confidence: 99%
“…Until now, this coefficient of mass sensitivity was evaluated using the perturbation theory and/or numerical methods such as the finite element method, etc. [21][22][23][24][25][26]. In this paper, to evaluate the mass sensitivity, we used analytical methods that provide a deeper insight into the physical background of the operation of Love wave sensors [19,20].…”
Section: Coefficient Of Mass Sensitivity S V P σmentioning
confidence: 99%
“…To overcome these challenges, an optimized surface acoustic wave (SAW)-based multiple-layer sensor and passive electrode potential sensor was integrated with microfluidic 96-well plates and fabricated by traditional microfabrication techniques. Full optimization of the sensor settings and the flow rate was conducted by finite element analysis to increase the sensitivity and generate appropriate shear stress on cells [63][64][65][66]. It was found that a fiber inspired smart scaffold (FiSS) platform established in the Mohapatra laboratory allows for the growth of 3D tumor-like aggregates (tumoroids), which resemble in vivo tumors [67].…”
Section: Tissue Engineeringmentioning
confidence: 99%